1997
DOI: 10.1159/000310799
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Lens Opacity Progression on Visual Acuity and Refraction

Abstract: The purpose of the present study was to evaluate the change in visual acuity and refraction taking place in eyes with progressing early lens opacities. Four hundred and ten hypercholesterolemic men in Eastern Finland who participated in the Kuopio Atherosclerosis Prevention Study were followed up for 3 years. Lens opacities were graded using the lens opacity classification system II (LOCS II). The change of visual acuity and refractive error from baseline to a 36-month examination was compared for different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Planter 6 suggested that cortical opacity can induce significant hyperopic shifts, but this claim has not been repeated. 7 Review papers have suggested that cortical opacity can induce astigmatic changes. 3 8 However, these reports were based on clinical impression with no supporting data.…”
mentioning
confidence: 99%
“…Planter 6 suggested that cortical opacity can induce significant hyperopic shifts, but this claim has not been repeated. 7 Review papers have suggested that cortical opacity can induce astigmatic changes. 3 8 However, these reports were based on clinical impression with no supporting data.…”
mentioning
confidence: 99%
“…Elliott et al found that some of their patients with extensive cortical opacity retained excellent visual acuity and attributed this to the ability to look through a “hole” in the cataract 11. Rouhiainen et al found that a decrease in Snellen acuity was associated with increasing nuclear opacification but not with early cortical opacity 10. Pesudovs and Coster found that a score of visual disability in cataract patients was related to nuclear opacity and to posterior subcapsular cataract but not to cortical cataract 12…”
Section: Discussionmentioning
confidence: 99%
“…Cyanopeptolins A (44) -D were isolated from Microcystis sp. 119 The depsipeptide is constructed using the standard NRPS machinery by genes apdA, B, and D, which contained two, four, and one NRPS modules, respectively. Structures were solved by a combination of amino acid analysis, GC, and 2D NMR, with total correlation spectroscopy (TOCSY) experiments proving crucial in the structural determination of the unusual Ahp residue.…”
Section: Cyanopeptolinsmentioning
confidence: 99%